O conhecimento dos médicos sobre a atuação fonoaudiológica pré e pós-operatória de gastroplastia em um município do Rio Grande do Sul (Brazilian Journal of Health Research, 2018)
Knowledge and awareness among physicians of the role of phonoaudiology in pre and post-operative gastroplasty in a city of Rio Grande do Sul